Pilot Study of Physiologic Partograph Use Among Low‐Risk, Nulliparous Women With Spontaneous Labor Onset. (24th February 2016) - Neal, Jeremy L.; Lowe, Nancy K.; Nacht, Amy S.; Koschoreck, Kate; Anderson, Jessica
Abstract : Introduction: Neal and Lowe developed a physiologic partograph to give clinicians an evidence‐based, uniform approach to assessing active labor progress and diagnosing dystocia in high‐resource settings. The aim of this pilot study was to examine the feasibility of implementing the Neal and Lowe partograph for in‐hospital labor assessment. Methods: A descriptive study of low‐risk, nulliparous women with spontaneous labor onset was performed at an academic medical center. Eight certified nurse‐midwives from a single practice used the Neal and Lowe partograph for the assessment of labor progress. Descriptive statistics were used to summarize characteristics, interventions, and outcomes for women with partograph‐assessed labors. Labors assessed by nurse‐midwives (n = 83) or obstetricians (n = 75) using their usual assessment strategies were also described for the year prior to partograph introduction to contextualize partograph‐assessed labor findings. Inferential statistical tests were not performed. Results: Thirty‐one of 34 (91.2%) partographs were used correctly. Seventy‐one percent (n = 22) of these women progressed to complete dilatation within expected physiologic time frames while the remaining women (n = 9) experienced labor dystocia. Similar proportions of women in the partograph and usual labor assessment groups received oxytocin during labor. The cesarean rate was lower in the partograph group than in the usual care groups. No cesareans were performed for dystocia in active labor for women whose labors were assessed via partograph. Discussion: Implementation of the Neal and Lowe partograph for in‐hospital labor assessment is feasible. Incorrect plotting and/or interpretation of the partograph may be further minimized by providing clinicians opportunities for ongoing partograph training after implementation or through partograph software development. The Neal and Lowe partograph may assist clinicians in safely and significantly decreasing primary cesarean births performed for active labor dystocia in high‐resource settings. Larger scale, hypothesis‐testing studies of partograph implementation are now warranted.